Pengaruh Penerapan Sistem Akuntansi Keuangan Desa Terhadap Kualitas Laporan Keuangan - Ningko, Trislawati; Budiawan, Shella (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study aims to find to what extent the effect of the Village Financial Accounting System on the Quality of Financial Reports of village apparatuses in Bolaang Uki Subdistrict, South Bolaang Mongondow District. The results show that the Village Financial Accounting System simultaneously has a positive and significant effect on the Quality of Financial Reports of village apparatus in Bolaang Uki Subdistrict, South Bolaang Mongondow District, Namely 0.709 (70.9%). The other variables unexplored explain the remained value of 0.291 (29.1%). The suitability of the Financial Accounting System (X1) BY 0.236 (23.6%), Transaction Recording Procedures (X2) by 0.242 (24.2%), Preparation of Financial Statement (X3) by 0.231 (23.1%) partially affect Reprt Preparation Finance (Y).